Engineering silk fibroin-based nerve conduit with neurotrophic factors for proximal protection after peripheral nerve injury - Carvalho, Cristiana R. (2020)
Artificial nerve conduits capable of adequately releasing neurotrophic factors are extensively studied to bridge nerve defects. However, the lack of neurotrophic factors in the proximal area and their visible effects in axonal retrograde transport following nerve injury is one of the factors causing an incomplete nerve regeneration. Herein, an advanced conduit made of silk fibroin is produced, which can incorporate growth factors and promote an effective regeneration after injury. For that, enzymatically crosslinked silk fibroin-based conduits are developed to be used as a platform for the controlled delivery of neurotrophic factors. Nerve growth factor and glial-cell line derived neurotrophic factor (GDNF) are incorporated using two different methodologies: i) crosslinking and ii) absorption method. The release profile is measured by ELISA technique. The bioactivity of the neurotrophic factors is evaluated in vitro by using primary dorsal root ganglia. When implanted in a 10 mm sciatic nerve defect in rats, GDNF-loaded silk fibroin conduits reveal retrograde neuroprotection as compared to autografts and plain silk fibroin conduit. Therefore, the novel design presents a substantial improvement of retrograde trafficking, neuronsâ protection, and motor nerve reinnervation.